Thinking against trauma binaries: the interdependence of personal and collective trauma in the narratives of Bosnian women rape survivors - Rajiva, Mythili; Takševa, Tatjana (Feminist theory, 2021)
In this article, we draw on feminist trauma studies with the aim of deconstructing the theoretical and methodological binary between individual and collective trauma. Based on first-hand interviews with Bosnian survivors of rape, we attempt to ‘think against’ the private/public split that trauma studies work often unintentionally reifies. We draw upon recent methodological innovations that have been influenced by thinkers such as Derrida and Deleuze. Specifically, we work with what Jackson and Mazzei call rhizomatic and trace readings in the threshold. Through a rhizomatic and trace reading of narrative pieces extracted from the interviews, we engage with the following questions: 1) How do we theorise what Davoine and Gaudilliere call ‘the sociopolitical faultlines’ between collective/public accounts of trauma and those traditionally constructed as private/personal? 2) How do accounts of war rape, which narrate the eruption of the past into the present, elucidate the myriad links between the private and public in a number of ways; among others, the echoes or traces of the everyday ‘before’ in subjects’ stories of the monstrous ‘after’? And 3) What is the relationship between the ‘unspeakable’ in the traumatic memories of the survivors and the ‘speakable’ collective memories of traumatic humanmade events? How does the collective desire ‘not to know’ or ‘to forget’ impact on the individual survivor’s ability to reconstitute their post-trauma identity in a personal as well as a social context? The aim of the analysis is to show that the multifaceted nature of the traumatic reality demands a multifaceted approach that resists binary constructions relating to self/other, private/public, individual/collective.